2015
DOI: 10.1038/gt.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound-targeted microbubble destruction to transfect IGF-1 cDNA to enhance the regeneration of rat wounded Achilles tendon in vivo

Abstract: The purpose of this study was to determine whether using ultrasound-targeted microbubble destruction (UTMD) to transfect rat wounded Achilles tendon with insulin-like growth factor-1 (IGF-1) cDNA would enhance tissue regeneration. Forty rats with injured Achilles tendons were transfected with IGF-1 cDNA and divided into: (1) control group, (2) plasmid-only group, (3) plasmid+ultrasound group and (4) plasmid+microbubbles+ultrasound group. The IGF-1 cDNA expression of the Achilles tendons was evaluated by histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Whether expression of transgenes will be switched off in patients would need careful evaluation when this treatment is moved to clinical trial in future, because immune responses is absent if human VEGF gene is introduced to the patients. A few recent studies highlighted non-viral or physical approaches to introduce genes to the Achilles tendon, an extrasynovial tendon 44 45 . Our group also used nanoparticles to deliver genes to tendons to inhibit adhesion formation 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether expression of transgenes will be switched off in patients would need careful evaluation when this treatment is moved to clinical trial in future, because immune responses is absent if human VEGF gene is introduced to the patients. A few recent studies highlighted non-viral or physical approaches to introduce genes to the Achilles tendon, an extrasynovial tendon 44 45 . Our group also used nanoparticles to deliver genes to tendons to inhibit adhesion formation 46 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, IGF‐I can promote the proliferation and migration of fibroblasts in injured sites, contribute to the synthesis of collagen in T/L, and assist tissue healing (Hansen et al, 2013; Tang et al, 2015). Steinert et al (2008) used an adenoviral vector to transfer IFG‐1 cDNA to a collagen hydrogel to deliver genes in situ into the damaged ligament.…”
Section: Engineering Methodsmentioning
confidence: 99%
“…Studies demonstrated that UTMD could increase the expression of genes in the Achilles tendon [99][100][101]. For example, Tang et al transfected injured Achilles tendons of mice with insulin-like growth factor-1 (IGF-1) cDNA, showing that the maximum load, stiffness, and ultimate stress of treated Achilles tendons were higher than control group [102]. Bez et al transferred BMP-6 encoding DNA by UTMD in Yucatan mini-pigs, showing the significantly enhanced osteointegration of all pigs after 8 weeks [103].…”
Section: Musculoskeletal Diseasementioning
confidence: 99%